2022
DOI: 10.3390/ijms23073875
|View full text |Cite
|
Sign up to set email alerts
|

Rotamers in Crystal Structures of Xylitol, D-Arabitol and L-Arabitol

Abstract: Rotamers are stereoisomers produced by rotation (twisting) about σ bonds and are often rapidly interconverting at room temperature. Xylitol—massively produced sweetener—(2R,3r,4S)-pentane-1,2,3,4,5-pentol) forms rotamers from the linear conformer by rotation of a xylitol fragment around the C2–C3 bond (rotamer 1) or the C3–C4 bond (rotamer 2). The rotamers form two distinguishable structures. Small differences in geometry of rotamers of the main carbon chain were confirmed by theoretical calculations; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Xylitol crystals were found to show two conformational patterns, in which φ2/φ3 = 60°/180° ( n = 33) or 180°/60° ( n = 12). It has been suggested that xylitol has two patterns of stable conformations [ 10 ]. The left- and right-handed bent conformations must be equally probable due to the symmetrical property of xylitol [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Xylitol crystals were found to show two conformational patterns, in which φ2/φ3 = 60°/180° ( n = 33) or 180°/60° ( n = 12). It has been suggested that xylitol has two patterns of stable conformations [ 10 ]. The left- and right-handed bent conformations must be equally probable due to the symmetrical property of xylitol [ 22 ].…”
Section: Resultsmentioning
confidence: 99%